2020
DOI: 10.47423/turkishstudies.44131
|View full text |Cite
|
Sign up to set email alerts
|

Biyoloji Öğretmen Adaylarının Genel Biyoloji Kavram Anlayışlarını Ölçmek İçin İki Aşamalı Tanı Testi Geliştirilmesi ve Uygulanması

Abstract: Scientific misconceptions are scientifically incorrect understandings or intuitions that negatively affect the learning and teaching process and are resistant to change. Teachers are one of the most common and important factors that cause students to develop misconceptions. The purpose of this study was to develop and implement a two-tier diagnostic test in order to identify prospective biology teachers' misconceptions and level of understandings of selected general biology concepts. The sample of the study (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Svandova (2014) determined, with the two-tier concept diagnostic test he developed for photosynthesis and plant respiration, that 6th, 7th, 8th and 9th grade students had many misconceptions such as plant respiration and photosynthesis are the same processes, photosynthesis occurs during the day and respiration occurs at night. Similarly, Uzunhasanoğlu et al (2020) determined, with the two-tier concept diagnostic test they developed for general biology topics, that prospective biology teachers had the misconception that plants photosynthesize during the day and respire at night. In their study with a two-tier test on the subject of photosynthesis, Atchia et al (2022) found that Secondary school Cambridge A level biology students had the misconception that photosynthesis occurs in the presence of light energy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Svandova (2014) determined, with the two-tier concept diagnostic test he developed for photosynthesis and plant respiration, that 6th, 7th, 8th and 9th grade students had many misconceptions such as plant respiration and photosynthesis are the same processes, photosynthesis occurs during the day and respiration occurs at night. Similarly, Uzunhasanoğlu et al (2020) determined, with the two-tier concept diagnostic test they developed for general biology topics, that prospective biology teachers had the misconception that plants photosynthesize during the day and respire at night. In their study with a two-tier test on the subject of photosynthesis, Atchia et al (2022) found that Secondary school Cambridge A level biology students had the misconception that photosynthesis occurs in the presence of light energy.…”
Section: Discussionmentioning
confidence: 99%
“…regarding respiration and photosynthesis in plants. As can be seen from all these studies conducted by Svandova (2014), Uzunhasanoğlu et al (2020), Atchia et al (2022), Urey (2018), Lin (2004) and Haslam and Treagust (1987), even though they are at different age groups and grade levels, students have an important misconception that sunlight is absolutely necessary for photosynthesis. The misconception coded M22, which was determined to be held by the 12th grade secondary school students with the four-tier SCDT developed for the concept of seed in this study, that the seed cannot photosynthesize in the light-free environment, is similar to the results of all these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation